Mysticism, Sufism, and Neurotheology: Bridging Spirituality and Modern Science - Atamimi, Muhamad (UIN Sunan Gunung Djati Bandung, 2025)
This article examines the integration of mysticism, spirituality, Sufism, and neurotheology as a means to bridge the spiritual and biological dimensions of human religious experience. Mysticism is interpreted as the pinnacle of transrational religious experience, while spirituality is viewed as a progressive development of ethical and inner consciousness. Sufism, as the mystical path of Islam, offers a structured and practical framework of spiritual ascent through concepts such as maqamat (stations), ahwal (states), dhikr (remembrance), and fana’ (ego dissolution). This study employs a qualitative approach, utilising a literature review and philosophical-interpretive content analysis, to examine classical Sufi texts and contemporary neuroscientific research. The findings suggest that Sufi practices are associated with specific neurological activities, including activation of the prefrontal cortex, increased theta waves, and decreased activity in the default mode network. The integration of Sufism and neurotheology supports the development of transdisciplinary models in spiritual education and psychological therapy, while maintaining epistemological boundaries and the depth of spiritual meaning. This article contributes to the interdisciplinary discourse of religious studies, opening up space for a constructive dialogue between revelation and science.